The interaction of phosphate and selenite in alkaline soil and accumulation by alfalfa (Medicago sativa L.) - Peng, Qi; He, Honghua; Fan, Chenbin; Wu, Miaomiao; Guo, Lei; Wang, Xia; Zhang, Xingchang (Archiv für Acker- und Pflanzenbau und Bodenkunde, 2021)
Selenium (Se) is an essential nutrient for humans and animals, but is toxic at high concentrations in leaves. It is chemically similar to phosphorus (P), an essential plant macronutrient. The objective of this pot experiment was to investigate the effects of P- and Se-application rate on alfalfa growth and P and Se uptake in loessial soil, and reveal the changing processes of soil P and Se fractions. The results indicated that Se concentration in alfalfa was significantly influenced by the interaction of P- and Se-application rate. In the loessial soil, an optimal P- and Se-application rate is 5 mg kg −1 and 2 mg kg −1 , respectively for plant growth and the maximum P and Se accumulation in alfalfa. Besides, concentrations of exchangeable Se and organic-matter-bound Se in soil decreased, as the P-application rate increased, whereas concentrations of soluble Se and iron oxide-bound Se increased. The addition of P fertilizer reduced soil pH, affecting the changing processes of soil P and Se fractions, thus promoting the activation of Fe-P and the transformation of exchangeable Se to iron oxide-bound Se. These findings will help in understanding of forage P and Se accumulation and provide the guide for cultivating Se-enriched forage.